Religious Foundations for the Protection of Civilians in Armed Conflicts: Scriptural Perspectives from Judaism, Christianity, and Islam - Alhelbawy, Sonia (Millah: Journal of Religious Studies, 2026)
Debates over the protection of civilians in times of armed conflict are often framed within political or legal discourse, yet their foundations lie deeply in religious and humanitarian ethics. This study contends that the obligation to safeguard non-combatants predates international law and is rooted in the moral teachings of the Abrahamic religions - Judaism, Christianity, and Islam. Rather than questioning the legitimacy of war itself, the paper focuses on affirming the right to life and dignity for those uninvolved in combat, deriving this principle from sacred scriptures that uphold the sanctity of human existence and peace. Through an analytical-inductive method, relevant texts from the Hebrew Bible, the New Testament, and the Qur’an, together with rabbinical writings, patristic sources, and prophetic traditions, are examined to extract ethical norms governing war-fare. A comparative reading highlights shared religious values that converge on the protection of civilians and the rejection of unjust violence. Employing a contextual reflective lens, the study connects these principles to present-day realities of war, seeking to awaken the global moral conscience toward the preservation of human life. The findings reveal that the Abrahamic faiths collectively provide a theological foundation for a universal humanitarian ethic that transcends religious and cultural divides.